Factor analysis: Investigating important aspects for agile adoption in Malaysia - Asnawi, Ani Liza; Gravell, Andrew M.; Wills, Gary B. (2012)
This paper focuses on identifying the important aspects of Agile adoption from software practitioners in Malaysia. We analyse 27 Agile adoption variables from a survey of early Agile users in Malaysia. Factor analysis is conducted to identify the clusters of the variables (or items) and how they are inter-related to produce factors. Most of the respondents are from software organisations in Kuala Lumpur and Selangor; in which most of the companies are located in Malaysia. The clusters of variables resulting from this analysis can serve as a reference to the practitioners planning to adopt the methodology. The top factors identified from this study are shown in terms of (i) developer involvement and organisation-related aspects, (ii) cultural and people related aspects and (iii) customer collaboration and the need for professional skills when using Agile methods. In addition, factor analysis discovered that practitioners disagreed about the importance of the technical aspects of Agile. While we believe that these findings are particularly important from the Malaysian perspective, however, they also help add to the body of evidence in the field of software engineering and software process particularly in terms of Agile methods adoption. Moreover, the study also can help adopters from the nearby geographical regions to understand and see the suitability of Agile methods for their organisations.